Effect of several parameters on ultrasound assisted extraction of carbohydrate from chlorella - Wang, Lei (2012)
Microalgae are one of the most hot-researched microorganisms. They contain many kinds of carbohydrates, protein, vitamins and other nutrients as well as many individual properties which make them suitable for many industrial fields.